Clinical researchAssessment of a single monomorphic ventricular ectopy from the right ventricular outflow tract in standard and high resolution electrocardiogram - Kozłowski, Dariusz; Kosiński, Adam; Dąbrowska-Kugacka, Alicja; Lewicka-Nowak, Ewa; Dudziak, Maria; Grzybiak, Marek; Raczak, Grzegorz (Archives of Medical Science, 2010)
Introduction: High-resolution electrocardiography (ECG-CREM) is a method based on digital electrocardiography. In order to facilitate the interpretation of the Crem records the technique of vectorcardiography was used. In comparison the origin of the ventricular premature complexes (VPCs) could be estimated based on a standard 12-lead electrocardiogram. The aim of the study was to assess the point of origin of the VPCs in ECG-CREM and correlate it with standard electrocardiography (ECG-Stand). Material and methods : Our study included 26 patients (16 females, 10 males), aged 51-83 years (avg. 58.1 ±12.3), who presented with recurrent, during at least 6 months’ observation, VPCs. The point of origin of VPCs was compared in both methods. Results: The performed analysis of collected ECG-Stand records revealed the presence of arrhythmogenic focal points in six different locations (1, 3, 5, 7, 8, 9). However, we did not affirm their presence in points 2,4,6. They were most commonly located in RVOT zones 8 (30.7%), 9 (23.0%), 5 (23.0%), and most seldom in zones 1, 3, 7 (7.6% each). In the simultaneous record of ECG-CREM with a single VPC it was confirmed that the FPb zone was activated the most frequently (40.0%); the next in relation to frequency were SD and ST (20.0%). Less frequent VPCs have their origin in Crem zones SP, FPa and SB (6.6%). Conclusions : Electrocardiogram of high signal resolution (ECG-CREM) might be useful in recognition of the origin of ventricular premature complexes from RVOT.